2010
DOI: 10.1159/000320792
|View full text |Cite
|
Sign up to set email alerts
|

Micronucleus in Cervical Intraepithelial Lesions and Carcinoma

Abstract: Aims and Objectives: To score and compare micronucleus (MN) in the whole spectrum of cervical lesions including normal, inflammatory, abnormal squamous cell of undetermined significance (ASC-US), low-grade squamous intraepithelial lesion (LSIL), high-grade squamous intraepithelial lesion (HSIL) and invasive cancer (IC) and to evaluate the role of MN as a biomarker in different pre-neoplastic and neoplastic lesions. Materials and Methods: A total of 224 slides, comprised of normal (40), inflammatory (40), ASC-U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
47
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(58 citation statements)
references
References 43 publications
(36 reference statements)
7
47
0
2
Order By: Relevance
“…We observed that suspicious cases had significantly higher MN frequency than reactive cases and lower MN frequency than malignant cases (P < 0.001). These findings are compatible with the results of other studies, which indicate that MN scoring is correlated to the grade of malignancy in breast aspirations and cervical smears (22,27,32). In addition, we found that MN counts in these suspicious cytological samples are correlated well with their final diagnoses (P < 0.001, with a power of 0.99).…”
Section: Suspicious Cytology (N = 22)supporting
confidence: 92%
See 1 more Smart Citation
“…We observed that suspicious cases had significantly higher MN frequency than reactive cases and lower MN frequency than malignant cases (P < 0.001). These findings are compatible with the results of other studies, which indicate that MN scoring is correlated to the grade of malignancy in breast aspirations and cervical smears (22,27,32). In addition, we found that MN counts in these suspicious cytological samples are correlated well with their final diagnoses (P < 0.001, with a power of 0.99).…”
Section: Suspicious Cytology (N = 22)supporting
confidence: 92%
“…Besides fine needle aspiration smears, the frequency of MN helped to detect atypical cells in urine samples and ascitic effusion, indicating malignancy (24,30,31). Moreover, our findings are consistent with the findings of studies on the frequency of MN in exfoliative, fine needle aspiration, and effusion smears (22,(25)(26)(27)(28)(29)(30)(31)(32)(33)(34).…”
Section: Suspicious Cytology (N = 22)supporting
confidence: 90%
“…Em face de nossos resultados, em que pese ao pequeno número de pacientes analisados, pudemos concluir que as pacientes HIV+ em fase de AIDS têm maior ocorrência de células micronucleadas do que a população controle e, também, a frequência com que são detectadas células micronucleadas parece se associar a piores condições clíni-cas da imunossupressão. Esses achados apoiam o proposto por Samanta et al 14 , que consideram o MN importante biomarcador para identificar condições pré-neoplásicas muito antes do estabelecimento de seus primeiros sinais clínicos. O acompanhamento em longo prazo das pacientes envolvidas no estudo, bem como a interpretação de outras variáveis, tais como o uso de terapêutica antirretroviral, permitirá analisar se efetivamente aquelas com maior número de MN evoluirão para lesões cervicais mais frequentes e graves.…”
Section: Discussionunclassified
“…Podem ser considerados marcadores morfológicos de lesão celular com potencial genotóxico de desenvolvimento neoplásico [13][14][15] . Estes danos cromossômicos costumam ser causados pela exposição das células a diferentes agentes genotóxicos, como radiações ionizantes 15 , materiais químicos 16 ou substâncias biológicas 17 .…”
Section: Introductionunclassified
“…[1] Its presence in a cell is a sensitive indicator of chromosomal damage. A direct association between increased MN frequency and cancer development has already been reported in head and neck, [2] colonic, [3] cervical, [4] and urothelial malignancies.…”
Section: Introductionmentioning
confidence: 99%